Optimality Theory - mohammad dabir moghadam (Matn/Pizhūhī-i Adabī, 2004)
This article introduces the Optimality theory (=OT). OT has been an influential development within generative linguistics since early nineties . Although OT was initially developed as a phonological theory, it soon received acceptance in morphology and syntax. A number of generative linguists interested in functional explanations have also welcomed OT. The theory is considered to be beneficial for interdisciplinary studies as well. This article describes the emergence of OT within the perspective of the developments in linguistics